Sexual harassment : threat to working women - Chaudhary, Reena (New Delhi : Deep & Deep Publications, 2011)
Study conducted in Chandigarh, India.
Includes bibliographical references (p. [210]-224) and index.
Keywords: Sexual harassment of women -- India; Women employees -- India -- Psychology